2001
DOI: 10.1124/mol.59.1.30
|View full text |Cite
|
Sign up to set email alerts
|

SCH-202676: An Allosteric Modulator of Both Agonist and Antagonist Binding to G Protein-Coupled Receptors

Abstract: A novel thiadiazole compound, SCH-202676 (N-(2,3-diphenyl-1,2, 4-thiadiazol-5-(2H)-ylidene)methanamine), has been identified as an inhibitor of both agonist and antagonist binding to G protein-coupled receptors (GPCRs). SCH-202676 inhibited radioligand binding to a number of structurally distinct, heterologously expressed GPCRs, including the human mu-, delta-, and kappa-opioid, alpha- and beta-adrenergic, muscarinic M1 and M2, and dopaminergic D1 and D2 receptors, but not to the tyrosine kinase epidermal grow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
76
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(82 citation statements)
references
References 35 publications
4
76
1
Order By: Relevance
“…Both amiloride analogues [21,34] and SCH-202676 [20,47] increased the dissociation rate of the antagonist [ 3 H]ZM241385 from the A 2A AR, while they did not show any effect on the dissociation rate of the agonist [ 3 H]CGS21680. The effects of these compound classes on dissociation kinetics were more pronounced at the A 2A AR than at other AR subtypes.…”
Section: A 2a and A 2b Arsmentioning
confidence: 97%
See 2 more Smart Citations
“…Both amiloride analogues [21,34] and SCH-202676 [20,47] increased the dissociation rate of the antagonist [ 3 H]ZM241385 from the A 2A AR, while they did not show any effect on the dissociation rate of the agonist [ 3 H]CGS21680. The effects of these compound classes on dissociation kinetics were more pronounced at the A 2A AR than at other AR subtypes.…”
Section: A 2a and A 2b Arsmentioning
confidence: 97%
“…Other allosteric modulators (Fig. (5)) for A 1 ARs include amiloride derivatives [21], the nonselective modulator of GPCRs SCH-202676 (35, N-(2,3-diphenyl-1,2,4-thiadiazol-5(2H)-ylidene)methanamine) [20,47], and sodium ions [22]. These are nonselective allosteric modulators, as they also modulate other adenosine receptor subtypes and other GPCRs [3].…”
Section: A 1 Arsmentioning
confidence: 99%
See 1 more Smart Citation
“…These modulators include SCH-202676 [21][22][23], amiloride analogues [24][25][26], agmatine [27]. The results suggested that for the P2Y 1 receptor, modes of interaction of orthosteric and allosteric binding sites might be different from that of other GPCRs.…”
Section: Discussionmentioning
confidence: 99%
“…2), was identified as an allosteric modulator of a variety of GPCRs, including mAChRs (Fawzi et al, 2001). This finding was based on radioligand binding assays performed on membrane preparations derived from cells transfected to individually express different types of GPCRs.…”
mentioning
confidence: 99%